Reuterin-producing Limosilactobacillus reuteri: Optimization of in situ reuterin production in alginate-based filmogenic solutions - F.J. Rodrigues (Elsevier, 2021)
Limosilactobacillus reuteri produces reuterin via glycerol anaerobic fermentation. This compound has antimicrobial properties and is used for food preservation purposes. Filmogenic solutions constituted of polysaccharides and glycerol are also employed, however, reuterin synthesis in filmogenic solutions has not yet been reported. Thus, the aim of this study was to optimize the in situ reuterin production by L. reuteri in alginate- and glycerol based-filmogenic solution, evaluating the survival of reuterin-producing bacteria during fermentation. The study consisted of a completely randomized design employing two L. reuteri strains (DSM 20016 and DSM 17938). The filmogenic solutions were obtained using sodium alginate (20 g/L) and two independent variables were studied: glycerol (0–300 mmol/L) and initial biomass of L. reuteri (≅6, 7, and 8 log CFU/mL). The samples were analyzed every 24 h for 72 h of anaerobic fermentation (37 °C). Both L. reuteri strains confirmed the potential for reuterin production and were susceptible to the metabolite produced. The highest reuterin production was achieved using L. reuteri DSM 20016. The initial microbial biomass of 8 log CFU/mL and 100 mmol/L of glycerol increased the reuterin production. However, higher conversion yields from glycerol to reuterin were obtained using 50 mmol/L of substrate.